The state of health in flood-prone areas in the Philippines: The case on the cities of Iligan and Cagayan de Oro - Clamor, Wilfred Luis (Animo Repository, 2020)
The Philippines suffers frequent typhoons every year hence the country is susceptible to experience disastrous flooding. This extreme event causes various effects in the community specifically infrastructural and social system damages. Flooding also causes numerous health effects that deteriorate the wellbeing of the affected population. Iligan City is known to be an area prone to flooding in the Philippines. This paper examines the state of health of communities affected by flooding occurrences through knowledge and preparedness, health impacts, and emergency response of various state actors during and after flooding incidents. Data were collected through an analysis of different documents, key informant interviews, and focus groups in the cities of Iligan and Cagayan de Oro. Results show data from various sources and narratives regarding the degree of preparedness before the flood among community members. During the flooding occurrence, different community damages were mentioned. Due to the destructive nature of floods, community members also stated different health impacts whether immediate, short term, or long term. After the flood, different emergency response and relief were provided. However, citizens and community also cited difficulties about the provision of relief and health care. This study can be used for initiatives in reducing risks and vulnerability in floods. © 2020 Taylor & Francis Group, LLC.